2013
DOI: 10.1146/annurev-pharmtox-011112-140320
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nrf2 in Oxidative Stress and Toxicity

Abstract: Organismal life encounters reactive oxidants from internal metabolism and environmental toxicant exposure. Reactive oxygen and nitrogen species cause oxidative stress and are traditionally viewed as being harmful. On the other hand, controlled production of oxidants in normal cells serves useful purposes to regulate signaling pathways. Reactive oxidants are counterbalanced by complex antioxidant defense systems regulated by a web of pathways to ensure that the response to oxidants is adequate for the body's ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
2,785
2
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,793 publications
(2,869 citation statements)
references
References 172 publications
(224 reference statements)
61
2,785
2
21
Order By: Relevance
“…Nrf2 is a master transcription factor in protecting cells from oxidative stress by orchestrating the expression of oxidative stress‐related genes 25. Importantly, previous studies also demonstrated that Nrf2 is indispensable for neuronal differentiation 26.…”
Section: Resultsmentioning
confidence: 99%
“…Nrf2 is a master transcription factor in protecting cells from oxidative stress by orchestrating the expression of oxidative stress‐related genes 25. Importantly, previous studies also demonstrated that Nrf2 is indispensable for neuronal differentiation 26.…”
Section: Resultsmentioning
confidence: 99%
“…Knockout of Lamp2a or Nfe2l2 makes cells more susceptible to different stressors [8,32], indicating a crucial role in the maintenance of cell homeostasis under different circumstances. In fact, previous work supports the notion that redox status tightly controls CMA activity, presumably to eliminate proteins oxidized during mild oxidative damage [14].…”
Section: Discussionmentioning
confidence: 99%
“…Lambertucci et al [80] reported that the changes in antioxidant enzyme activities were associated with antioxidant enzyme gene transcription in rat. In fish, Nrf2 has been demonstrated as a critical transcription factor that promotes the transcription of antioxidant enzyme genes by binding to the antioxidant response element in the promoter region of these antioxidant enzyme genes [81]. Thus, in order to further elucidate the underlying mechanism by which dietary Phe enhances the antioxidant capacity to protect intestinal integrity in fish, we next investigated the effect of Phe on the gene expression of antioxidant enzymes and signal molecules Nrf2 and Keap1 in the intestines of young grass carp.…”
Section: Phe Regulated Tj Protein Transcript Abundance In the Intestimentioning
confidence: 99%